Erwartungen an RIO 2016 - Die Perspektive lateinamerikanischer Stakeholder - Ferreira dos Santos, L. C.; Hodeck, A.; Hovemann, G. (Leipziger Sportwissenschaftliche Beiträge, 2016)
Mega sport events and especially Olympic Games have been in the focus of scientific work since years. There are a lot of publications dealing with effects, impacts or the legacy of them. Most of the authors concentrate on economic aspects in that field. This study uses a stakeholder approach and tries to examine the whole range of the Olympic and Paralympic Games of Rio 2016 by using a qualitative research method. Stakeholders from Latin-America are asked about their expectations regarding the first Games in South-America. Later on the expectations will be compared with their actual experiences.